2013
DOI: 10.1161/atvbaha.113.301857
|View full text |Cite
|
Sign up to set email alerts
|

Bis(Monoacylglycero)Phosphate Accumulation in Macrophages Induces Intracellular Cholesterol Redistribution, Attenuates Liver-X Receptor/ATP-Binding Cassette Transporter A1/ATP-Binding Cassette Transporter G1 Pathway, and Impairs Cholesterol Efflux

Abstract: Objective— Endosomal signature phospholipid bis(monoacylglycero)phosphate (BMP) has been involved in the regulation of cellular cholesterol homeostasis. Accumulation of BMP is a hallmark of lipid storage disorders and was recently reported as a noticeable feature of oxidized low-density lipoprotein–laden macrophages. This study was designed to delineate the consequences of macrophage BMP accumulation on intracellular cholesterol distribution, metabolism, and efflux and to unravel the underlying mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In addition, storage of sphingosine causes a loss in lysosomal calcium regulation which slows the rate at which autophagic vacuoles are processed by LE/Lys (Lloyd-Evans and Platt, 2010). Mechanism DIPL results in changes in lysosomal function (Kobayashi et al, 1998;Tengstrand et al, 2010) and cholesterol status (Chevallier et al, 2008;Luquain-Costaz et al, 2013;Xu et al, 2008) that are observed in NPC disease. CADs inhibit the activities of phospholipases A and C and lysosomal enzymes that are deficient in sphingolipidoses (i.e., aSMase (Niemann-Pick), acid ceramidase (Farber), acid lipase (Wolman)) (Kornhuber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, storage of sphingosine causes a loss in lysosomal calcium regulation which slows the rate at which autophagic vacuoles are processed by LE/Lys (Lloyd-Evans and Platt, 2010). Mechanism DIPL results in changes in lysosomal function (Kobayashi et al, 1998;Tengstrand et al, 2010) and cholesterol status (Chevallier et al, 2008;Luquain-Costaz et al, 2013;Xu et al, 2008) that are observed in NPC disease. CADs inhibit the activities of phospholipases A and C and lysosomal enzymes that are deficient in sphingolipidoses (i.e., aSMase (Niemann-Pick), acid ceramidase (Farber), acid lipase (Wolman)) (Kornhuber et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…When we examine these features individually, we can see a differential response to infection for males and females (for instance, PG 18:1_18:2, a glycerophospholipid) represented in Supplemental Figure 2C). Seven of the 20 molecular features identified by machine learning are BMP (Bis(monoacylglycerol)phosphate) species, which have been implicated in glycosphingolipid degradation and cholesterol transport [54, 55]. These data further support the hypothesis that S. mansoni infection differentially modulates the metabolism of myeloid cells from male and female animals, and that this modulation revolves around decreased cholesterol storage and fatty acid synthesis in males and increased cholesterol storage and fatty acid synthesis in females.…”
Section: Resultsmentioning
confidence: 68%
“…2B). Additionally, ORP11 labelling also colocalized with BMP (M2 = 0.91 ± 0.05), known to be an endosomal resident in RAW264.7 macrophages and representing a typical punctated perinuclear pattern [17], consistent with a possible cooperation between these two factors involved in sterol trafficking.…”
Section: Orp11 a Candidate Implicated In Bmp-mediated Oxysterol Trafficmentioning
confidence: 57%
“…Another important effector of oxysterols is bis(monoacylglycero) phosphate (BMP), a phospholipid preferentially found in LE membranes. BMP participates in cholesterol metabolism/trafficking in macrophages and regulates cholesterol efflux to HDL [5,[14][15][16][17]. We recently showed that BMP exerts a protective action against the proapoptotic effect of oxLDL via a reduced production of intracellular oxysterols [5], but the underlying molecular mechanism remains to be characterized.…”
Section: Introductionmentioning
confidence: 99%